2018
DOI: 10.1111/1346-8138.14193
|View full text |Cite
|
Sign up to set email alerts
|

Association between allergic diseases and ophthalmologic diseases, including cataracts and glaucoma, using the Korean National Health and Nutrition Examination Survey 2010–2012: A STROBE‐compliant article

Abstract: This study investigated the association between allergic diseases and comorbid ophthalmologic diseases. We enrolled 14 776 participants who were at least 19 years of age. Multiple logistic regression analyses were used to evaluate the odds ratios for cataracts and glaucoma according to the presence of allergic diseases. Atopic dermatitis was not associated with the development of cataracts and glaucoma. However, asthma and allergic rhinitis were significantly associated with cataracts (hazard ratio [HR] = 1.51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Some studies indicate that asthma may positively impact the development of cataract. What we have found in this study is identical with those who have estimated the relationship between these two diseases [ 7 , 8 , 14 , 15 ]. Zhao et al found that when establishing asthma model of rats, asthmatic rats were more likely to develop monocular or binocular cataract than normal rats.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies indicate that asthma may positively impact the development of cataract. What we have found in this study is identical with those who have estimated the relationship between these two diseases [ 7 , 8 , 14 , 15 ]. Zhao et al found that when establishing asthma model of rats, asthmatic rats were more likely to develop monocular or binocular cataract than normal rats.…”
Section: Discussionsupporting
confidence: 91%
“…The following two cross-sectional population-based studies using the same database obtained from the Fifth Korean National Health and Nutrition Examination Survey (KNHANES-V, 2010-2012) showed different results 8,9 . Lee et al 9 investigated the association between cataract development and allergic diseases in a population aged > 19 years.…”
Section: Discussionmentioning
confidence: 97%
“…The following two cross-sectional population-based studies using the same database obtained from the Fifth Korean National Health and Nutrition Examination Survey (KNHANES-V, 2010-2012) showed different results 8,9 . Lee et al 9 investigated the association between cataract development and allergic diseases in a population aged > 19 years. Cataract was defined as a history of ophthalmology or cataract surgery, and allergic diseases were defined as "yes" responses to the questions of diagnostic history.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, another recent population-based study using the Korean National Health and Nutrition Examination Survey reported that cataracts were associated with asthma and allergic rhinitis, but not with AD, in a cohort of adults with allergic diseases. 6 Jeon et al 5 classified patients as having severe AD when they received any treatment within a year of the index date with omalizumab, intravenous immunoglobin, interferon γ, or rituximab or 2 or more weeks of cyclosporine, azathioprine, mycophenolate mofetil, methotrexate, or systemic steroids. Since intravenous immunoglobin, interferon γ, and rituximab are rarely used to treat severe AD, it is possible that some of the patients were misclassified as having severe AD when in fact they had other autoimmune diseases.…”
Section: Invited Commentarymentioning
confidence: 99%